MB‐UiO‐66‐NH2 Metal‐Organic Framework as Chromogenic and Fluorogenic Sensor for Hydrazine Hydrate in Aqueous Solution. Issue 25 (4th September 2017) - Helal, Aasif; Qamaruddin, Muhammad; Aziz, Muhammad A.; Shaikh, Muhammad N.; Yamani, Zain H.
Abstract: Zirconium(IV)‐based MOFs UiO‐66‐NH2 and UiO‐66‐NH2 encapsulated with methylene blue (MB) MB‐UiO‐66‐NH2 were successfully prepared using a facile solvothermal method and were characterized by X‐ray diffraction (XRD), transmission electron microscopy (TEM), field emission scanning electron microscopy (FESEM), nitrogen physisorption analysis (BET), and X‐ray and photoelectron spectroscopy(XPS). Both the materials were 60–80 nm size and had large surface areas. MB‐UiO‐66‐NH2 appears to be a potential candidate for the sensing of hydrazine hydrate. Selective changes in both the chromogenic and fluorogenic characteristics of MB‐UiO‐66‐NH2 were observed upon treatment with hydrazine hydrate in an aqueous solution. The change in the photophysical properties of the MB‐UiO‐66‐NH2 was attributed to the selective conversion of methylene‐blue‐encapsulated UiO‐66‐NH2 to leucomethylene blue (LB) after the addition of hydrazine hydrate to the aqueous solution. The hydrazine hydrate detection limit for MB‐UiO‐66‐NH2 was found to be 0.012 ppm in the aqueous solution. Abstract : Zirconium(IV)‐based MOFs UiO‐66‐NH2 and UiO‐66‐NH2 encapsulated with methylene blue MB‐UiO‐66‐NH2 were successfully prepared which act as a potential candidate for the chromogenic and fluorogenic sensing of hydrazine hydrate in aqueous solution. The hydrazine hydrate detection limit for MB‐UiO‐66‐NH2 was found to be 0.012 ppm in the aqueous solution.